Mediating Misogyny Gender, Technology, and Harassment (Springer International Publishing, 2018)
Mediating Misogyny is a collection of original academic essays that foregrounds the intersection of gender, technology, and media. Framed and informed by feminist theory, the book offers empirical research and nuanced theoretical analysis about the gender-based harassment women experience both online and offline. The contributors of this volume provide information on the ways feminist activists are using digital tools to combat harassment, raise awareness, and organize for social and political change across the globe. Lastly, the book provides practical resources and tips to help students, educators, institutions, and researchers stop online harassment.